SOCIAL EXPRESSIONS AND SOCIAL ABILITIES OF JUNIOR HIGH SCHOOL STUDENTS - Acat, Ezelle Rose Caula (IDEAS: Journal of Management & Technology, 2025)
One of the largest impacts the pandemic has had on children's lives is the limited opportunities to interact with peers. In many societies, young children stayed home with their families, and less focus was put on interactions with other people. The study aimed to determine the Degree of Social Expression and Social Abilities of Junior High School students in Colegio de la Purisima Concepcion for the academic year 2023-2024. Foreign and local literature on social expressions and social abilities were reviewed with their relevance and implication to the study. A validated and reliability-tested researcher-made questionnaire was used to gather data from randomly selected respondents. Statistical tools used to analyze and interpret data were frequency count, percentage, mean, grand mean, t-test, f-test, and Pearson R. The study's findings revealed the degree of social expressions and the extent of social abilities were â€œoftenâ€. There was a significant difference in the degree of social expressions when the respondents were grouped according to the curriculum program. There was no significant difference in the extent of social abilities when the respondents were grouped according to age, sex, grade level, curriculum program, ordinal position in the family, and family living arrangement. And the degree of social expressions was significantly related to the extent of social abilities. Results suggest a deeper understanding of the impact of social expressions on students' social abilities.Â